Preparation and Photocatalytic and Antibacterial Activities of Micro/Nanostructured TiO2-Based Photocatalysts for Application in Orthopedic Implants - Qi, Liang; Guo, Binghua; Lu, Qing; Gong, Hanghui; Wang, Min; He, Jinlong; Jia, Bin; Ren, Jing; Zheng, Shicheng; Lu, Yufeng (Frontiers in Materials, 2022)
Abstract: Micro/nano-structured TiO2, ion-doped TiO2 and heterojunction TiO2 composite photocatalysts have low toxicity, high biocompatibility, high photocatalytic activity and antibacterial activity, and have broad applications in the field of photocatalytic, antibacterial and orthopedic implants. The photocatalytic activity and antibacterial activity of TiO2 and TiO2-based photocatalysts depend on their preparation methods. In this review, the preparation methods of TiO2, ion-doped TiO2 and heterojunction TiO2 composite photocatalysts were reviewed, and their effects on photocatalytic activity and antibacterial activity were reviewed. Based on the excellent physical and chemical properties of TiO2, ion-doped TiO2 and heterojunction TiO2 based photocatalysts, their applications in the field of orthopedic implants were reviewed. Meanwhile, the development trend of the photocatalyst in the fields of photocatalysis, bacteriostasis and medicine was prospected. The purpose of this review is to point out the direction for the further study of photocatalytic activity, antibacterial activity and related applications of TiO2 and TiO2-based photocatalysts.